Drugs in sport - 4 0 16; (David R.), 1944- Mottram, D. R.; 5 (London ;;New York : E & FN Spon, 1996)
Presents scientific descriptions of several drugs' effects on the human body, including their effects on athletic performance, and discusses their status as banned drugs in athletics.
Includes bibliographical references and index.
Young Adult;Young Adult.
Keywords: 2 -- 0; 6; Drug use. -- Doping in sports.;Athletes; 20; 2